Caring for critters : one year at a wildlife rescue centre - Read, Nicholas, 1956- (Heritage House Publishing, 2021)
"A colourful, engaging, and educational profile of a well-established wildlife rescue and rehabilitation centre, highlighting the heartwarming stories of animals and the people who care for them. Critter Care is a cute name for a life-saving organization. For over three decades, the wildlife rehabilitation centre in Langley, BC, has rescued and cared for more than 50,000 sick, injured, and orphaned animals--from bears to beavers, coyotes to cougars, rabbits to river otters, and skunks to squirrels. Author and journalist Nicholas Read spent one year volunteering at Critter Care, helping to take care of the animals and recording the stories of every furry friend who walked, hopped, or crept through their doors. Full of information, compassion, and a strong dose of social awareness, Caring for Critters is a month-by-month account of Read's experience. Through adorable photos and true stories--some uplifting, others sad--the book teaches children and young adults about the dangers that animals face as humans destroy the environment and invade natural habitats, and encourages kids to get involved in animal welfare and conservation."--